La educación ambiental en la enseñanza y aprendizaje en la educación básica - Pineda Cipagauta, Jhon Albeiro; Prieto González, Gladys Esperanza (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Environmental education is a training process that allows awareness of the conservation of the environment where values and positive attitudes that contribute to the rational use of natural resources are promoted. In this document, some conceptual referents about environmental education are projected and how this can be strengthened through learning and teaching didactics. Legal references are presented where the participation of the institutions is included as the main axis in the realization and execution of said projects. It is also emphasized that in the exercise as teachers of the area of natural sciences environmental education is developed according to guidelines such as the application of an environmental approach, a transversality articulated with educational projects, environmental committees, and communication and environmental educa- tion competencies.